1983
DOI: 10.1002/cyto.990040212
|View full text |Cite
|
Sign up to set email alerts
|

Non‐small‐cell lung carcinoma: Tumor characterization on the basis of flow cytometrically determined cellular heterogeneity

Abstract: Some 150 tumor specimens from 49 patients with non-small-cell carcinoma of the lung (23 epidermoid, 14 adenocarcinoma, 12 large-cell carcinoma) and three with nonneoplastic lung disease were analysed for cellular DNA content by flow cytometry. Monodispersed cells were stained with ethidium bromide and mithramycin. Normal specimens and samples from patients with nonneoplastic disease constantly yielded a single cell population with diploid DNA content. Twenty of 23 epidermoid carcinomas exhibited one or more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Flow cytometry provides a fast and precise method for determination of DNA ploidy and distribution of the cell cycle in tumors. Earlier studies of lung using flow cytometry have shown an aneuploid DNA content in 85% of the primary lung tumors (4,19,22,26,28). The clinical implication of DNA aneuploidy has been examined in various tumor types and in general has been associated with a poor prognosis (2,3,9,11,13,25,28,34).…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry provides a fast and precise method for determination of DNA ploidy and distribution of the cell cycle in tumors. Earlier studies of lung using flow cytometry have shown an aneuploid DNA content in 85% of the primary lung tumors (4,19,22,26,28). The clinical implication of DNA aneuploidy has been examined in various tumor types and in general has been associated with a poor prognosis (2,3,9,11,13,25,28,34).…”
Section: Discussionmentioning
confidence: 99%
“…One such factor is genetic instability, observed by geneticists and molecular biologists, which co-occurs with malignant tumors and is manifested through the abnormal DNA content of cancer cells. The first reports on the prognostic significance of aneuploidy (abnormal amount of DNA) in lung cancer date from the late 1980s [1][2][3][4]. The relatively few reports that have appeared since then are quite inconsistent as to the prognostic significance of ploidy [5][6][7][8][9] This research is a continuation of studies, the early results of which were published in 2000 and 2005 [10,11] The current focus is on the analysis of the effect of aneuploidy on 10-year survival rates in the group of patients treated surgically for squamous cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of flow cytometry it has become possible to study karyotypic abnormalities as reflected in DNA content (aneuploidy) in both haematological and solid tumors without being limited to the availability of metaphase cells. So far a correlation between aneuploidy and wellknown prognostic markers has been described for various solid tumors (1,(7)(8)(9)(10). Since DNA flow cytometry required until recently fresh unfixed material, the progress in studies relating aneuploidy to disease-free interval and overall survival has been slow.…”
mentioning
confidence: 99%